Effects of seabed morphology on oscillating water column wave energy converters. (15th September 2017) - Medina-López, E.; Bergillos, R.J.; Moñino, A.; Clavero, M.; Ortega-Sánchez, M.
Abstract: This paper presents a numerical model to analyse the effects of changes in the bedforms morphology on Oscillating Water Column (OWC) wave energy devices. The model was developed in FLUENT ® and based on the Actuator Disk Model theory to simulate the turbine performance. The seabed forms were reproduced with the morphodynamic model XBeach-G for a series of characteristic sea states in Playa Granada (southern Spain). These bedforms were used as input bed geometries in FLUENT ® and compared with a hypothetical flat seabed to analyse the effects of changes in bed level on the OWC performance. Results of the simulated sea states reveal the influence of the seabed morphology in the power take–off performance, affecting the relationship between pressure drop and air flow rate through the turbine. Energy dissipation was found to be directly dependent on the bedforms unit volume. This lead to lower mean efficiencies for the cases with evolved morphologies (up to 15 % ) compared to those obtained for the hypothetical flat cases ( 19 % ). The effects of seabed formations on the power take–off performance presented in this paper can be of interest in planning control strategies for OWC devices. Highlights: This paper studies the effects of seabed Morphology on OWC systems. A numerical model is presented to analyse the effects of bedforms changes on OWCs. The model is developed in Fluent ® and compared with a hypothetical flat seabed. The seabed is reproduced with XBeach-G ® for sea states in Playa Granada (Spain). Energy dissipation relates to bedform volume, decreasing efficiency for evolved seabeds.